Under the umbrella: Commentary on: Chaos and confusion in DSM-5 diagnosis of Internet Gaming Disorder: Issues, concerns, and recommendations for clarity in the field (Kuss et al.) - Müller, Kai W. (J Behav Addict, 2017)
The inclusion of Internet Gaming Disorder as a preliminary diagnosis subsumed in Section III of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) has provoked mixed reactions. On the one hand, it has been appreciated as an important sign stressing the negative health-related impact of that disorder. Likewise, the definition of diagnostic criteria helps scientists and clinicians to refer to mandatory indicators associated with a health problem. On the other hand, it has been objected that this new diagnosis bears the danger of pathologizing normal behaviors that are a feature of healthy recreational activity for many people. However, the existence of diagnostic criteria is meant to avoid this danger. This emphasizes the necessity of being able to refer to as accurate defined criteria as possible. In its current version, the DSM criteria display not only strengths but also ambiguities. Both types will be discussed and necessary ideas to resolve those ambiguities will be presented for further research.